Diet of the south polar skua Catharacta maccormicki and the brown skua C. antarctica lonnbergi at Cierva Point, Antarctic Peninsula - Malzof, Silvina L.; Quintana, Ruben Dario (Polar Biology)
South polar skuas, SPS, (Catharacta maccormicki) and brown skuas, BS, (C. antarctica lonnbergi) are regarded as opportunistic predators. When breeding in sympatry, BS feed mainly on penguin eggs and chicks, while SPS forage almost exclusively at sea. The objective of this study was to determine the diet composition of adult SPS and BS breeding in sympatry, in order to assess food resource partitioning between these species. The total number of food items consumed was 375 for BS and 682 for SPS in 1992–93, and 427 for BS and 579 for SPS in 1995–96. The pellets composition was significantly correlated between skua species for the same breeding season (rs = 0.67, p = 0.0062 and rs = 0.81, p\0.001, for 1992–93 and 1995–96, respectively), and between breeding seasons for the same skua species (rs = 0.71, p = 0.001 and rs = 0.81, p\0.001, for SPS and BS, respectively). Trophic niche breadth of BS was wider than that of SPS (BA(BS) = 0.28 and BA(SPS) = 0.24; Z = 7.67; p\0.001). The trophic niche overlap between BS and SPS was over 65% in both breeding seasons. In agreement with other studies on the diet of these skua species in situations of sympatry, SPS consumed more fish and BS consumed more birds. Fil: Malzof, Silvina L. Universidad de Buenos Aires. Facultad de Cs.exactas y Naturales. Departamento de Ecología, Genética y Evolución. Laboratorio de Ecología Regional; Argentina Fil: Quintana, Ruben Dario. Universidad de Buenos Aires. Facultad de Cs.exactas y Naturales. Departamento de Ecología, Genética y Evolución. Laboratorio de Ecología Regional; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina